Fostering Critical Thinking Through E-Worksheets: A Project-Based Approach to Fish Waste Processing Education - Perdana, Dheonardo Putra; Hasnunidah, Neni; Fadiawati, Noor; Jalmo, Tri (International Journal of Education, Culture, and Society, 2025)
Despite the importance of critical thinking in science education, junior high schools often lack effective instructional models that engage students with real-world environmental issues. One such issue, fish waste management, remains underutilised as a learning context, despite its relevance to local communities. This study investigates the effectiveness of project-based learning (PjBL) assisted by e-worksheets in fostering students’ critical thinking skills through the topic of fish waste processing. A quasi-experimental design was employed, involving 30 seventh-grade students in Bandar Lampung, Indonesia. Pre- and post-tests were administered to measure five core indicators of critical thinking: problem identification, information sourcing, hypothesis formulation, clarification, and solution generation. The results, analysed using SPSS 25.0, showed significant improvements across all indicators. For instance, accurate problem identification responses increased from 0% to 47%, and logical hypothesis construction improved from 0% to 37%. Students also reported greater engagement with the digital worksheets, which featured multimedia content, simulations, and open-ended questions. The findings indicate that e-worksheet-assisted PjBL is an effective pedagogical strategy for enhancing students’ analytical thinking, environmental literacy, and meaningful learning engagement across science education contexts.